Functionalized carrier systems for cellulose nanofibrils designed for polymer composites - Kiziltas, Alper; Han, Yousoo; Gardner, Douglas Jerome S.; Neivandt, David J.; Rushing, Todd S.; Nader, Jacques W. (My University, 2011)
[No abstract available]
TAPPI International Conference on Nanotechnology for Renewable Materials 2011 -- Washington, DC -- 89296
Keywords: [No Keywords]